A Nonparametric Partially Identified Estimator for Equivalence Scales - Christian Dudel (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
Methods for estimating equivalence scales usually rely on rather strong identifying assumptions. This paper considers a partially identified estimator for equivalence scales derived from the potential outcomes framework and using nonparametric methods for estimation, which requires only mild assumptions. Instead of point estimates, the method yields only lower and upper bounds of equivalence scales. Results of an analysis using German expenditure data show that the range implied by these bounds is rather wide, but can be reduced using additional covariates. – – Methoden zur Ermittlung von Äquivalenzskalen gehen in aller Regel von relativ starken Annahmen aus. In der vorliegenden Arbeit wird ein partiell identifizierter Schätzer für Äquivalenzskalen vorgestellt, der auf dem Potential Outcomes Ansatz basiert und nur vergleichsweise schwache Annahmen benötigt. Anstelle eines Punktschätzers liefert das Verfahren nur Unter- und Obergrenzen für Äquivalenzskalen. Eine Anwendung auf Daten der Einkommens- und Verbrauchsstichprobe zeigt, dass die durch Unter- und Obergrenze gegebenen Intervalle oftmals sehr breit sind. Die Breite der Intervalle kann reduziert werden, wenn zusätzliche Variablen bei der Schätzung herangezogen werden.
Keywords: C14; D12; 330; household equivalence scale; partial identification; matching estimator